The Asteraceae family in the Tepoztlán municipality, Morelos, Mexico - Espín Bahena, María Luisa; Cedillo Portugal, Ernestina; Villaseñor Rios, José Luis (Instituto de Ecología, A.C., 2023)
Background and Aims: The Asteraceae occupies a predominant place in the flora of Mexico and in many other parts of the world. The count of their number of species, genera, and tribes at a national scale can be considered reliable, but at a more local scale their knowledge is still deficient since there are still many unexplored areas. The objective of this work was to identify the diversity of Asteraceae species in the municipality of Tepoztlán, Morelos, Mexico, as well as to analyze their distribution in the main types of biomes recorded in the municipality, and documenting their conservation status. Methods: To document the floristic diversity of the municipality, a review of the literature as exhaustive as possible was carried out, in addition to the review of the herbarium material collected in the municipality and deposited in different collections (23 herbaria, mainly JES, MEXU, SLPM, and XAL). In addition, fieldwork to collect material from the family in different localities along the municipality was carried out. Key results: In the Municipality of Tepoztlán, Morelos, the existence of 256 species, distributed in 98 genera and 19 tribes, is documented; 121 species (47.3% of the total) are endemic to Mexico and four introduced (exotics). More than 170 botanists have made the collection effort in the municipality, but nine of them stand out for their greater number of collections. Due to their number of species, the tribes Eupatorieae (55) and Heliantheae (54) stand out, although due to their number of genera surpass Heliantheae (24), Millerieae (15), and Eupatorieae (11). The genera Ageratina and Stevia record the highest number of species (20 and 17 respectively). The temperate forests of the municipality display a greater collection effort, followed by the seasonally dry tropical forest; the fragments of humid montane forest are the least explored. Conclusions: Although the municipality is perhaps the best known in terms of its Asteraceae diversity species, the need to continue with the floristic inventory work is underlined.